Prevention of vagotonia and pain during radiofrequency ablation of liver tumors. Issue 13 (2nd April 2014) - Nakamura, Shinichiro; Nouso, Kazuhiro; Onishi, Hideki; Kuwaki, Kenji; Hagihara, Hiroaki; Takeuchi, Yasuto; Wada, Nozomu; Morimoto, Yuki; Miyahara, Koji; Yasunaka, Tetsuya; Ikeda, Fusao; Miyake, Yasuhiro; et al.
Abstract : Radiofrequency ablation (RFA) is frequently used to treat early stage hepatocellular carcinoma. Two of the most cumbersome side‐effects of the ablation procedure are intractable pain and vagotonia when deep sedation is not used. We describe local injection of anesthetic into Glisson's sheath as a new technique for overcoming these problems. Lidocaine was injected into Glisson's sheath when radiofrequency ablation of hepatocellular carcinomas, which were located adjacent to Glisson's sheath, could not be continued due to severe pain ( n  = 8) or bradycardia ( n  = 3). In all three patients who showed vagotonia with bradycardia during the ablations, injection of lidocaine prevented bradycardia, allowing completion of the radiofrequency ablation. Pain was reduced in all eight patients who experienced pain during ablation. No side‐effects were observed during the procedures. Injection of anesthetic into Glisson's sheath is simple and effective for reducing intractable pain and vagotonia associated with RFA.